Efficacy of metformin monotherapy in US veterans with type 2 diabetes and preexisting chronic kidney disease stage 3. Issue 8 (14th May 2021) - Gosmanov, Aidar R.; Gemoets, Darren E.; Kaminsky, Laurence S.; Kovesdy, Csaba P.; Gosmanova, Elvira O.
Abstract: Aim: To evaluate the glycaemic efficacy of metformin in people with type 2 diabetes (T2D) and stage 3 chronic kidney disease (CKD3). Participants and methods: This was a retrospective study including 145980 US veterans with T2D and an estimated glomerular filtration rate (eGFR) ≥30 mL/min/1.73 m 2 who initiated metformin monotherapy between November 1999 and July 2017. Propensity‐score‐matched cohorts were generated based on baseline variables associated with CKD3 (eGFR 30‐59 mL/min/1.73 m 2 ) to evaluate the independent association between CKD3 and metformin discontinuation, the addition of a second hypoglycaemic agent, and changes in glycated haemoglobin (HbA1c) from baseline in those with and without CKD3. Associations were examined using the Kaplan‐Meier method and multivariable regression models, adjusted for baseline and 12‐month average metformin dose. Results: The mean age of the entire cohort was 60.7 years, and 95% of the cohort were men, 21% were African American and 9% had CKD3. In the adjusted analyses, patients with CKD3 had a higher risk of metformin discontinuation or addition of a second hypoglycaemic agent, as compared with patients without CKD (hazard ratio [HR] 1.22, 95% confidence interval [CI] 1.19‐1.26, and HR 1.26, 95% CI 1.13‐1.40, respectively). Among metformin monotherapy users, there were no differences in the average HbA1c reduction from baseline to 12 or 24 months between patients with and without CKD3. Conclusions: Individuals with CKD3 and T2D were at increased risk of metformin monotherapy failure. However, the HbA1c‐lowering efficacy of metformin was similar in patients with and without CKD3, highlighting that metformin is a valuable treatment option for newly treated individuals with T2D and CKD3.